THE EFFECTS OF THE REPETITION METHOD ON SOME ABILITIES, BIOMECHANICAL VARIABLES, AND THE ACCURACY OF THE SKILL OF THE WALL SURFACE FACING THE ADVANCING BALL - Teaching Assistant. Laith Ali Mohammed (Proximus Journal Publishing, 2024)
By studying the values of biomechanical variables and seeking to develop those variables that have a major role in the performance of skills, including the offensive blocking wall skill, according to mechanical foundations and indicators, which give a good explanation of the values of some mechanical variables, which have a significant impact on skill performance through the amount of force applied, which helps to Gaining a large amount of the push indicator in a shorter time, which may have a positive role in the performance of the attacking blocking wall skill
Keywords: attacking; offensive; Gaining; indicator